How Managers Foster Trust Through Control and Trustworthiness - Long,Chs; Carroll,Tim; Holtom,Brooks (Academy of Management Proceedings, 2016)
This paper contributes to control-trust research by describing how the efforts managers make to demonstrate their trustworthiness (integrity, ability, benevolence) moderate the effects of managerial controls (output, process, social) on subordinate trust. Our survey of managers and subordinates indicates three conditions under which subordinate trust increases: when managers apply output controls and demonstrate their integrity; when managers apply process controls and demonstrate their ability; when managers apply social controls and demonstrate their benevolence. We argue that that these relationships exist because when managers demonstrate their trustworthiness in ways that facilitate the achievement of performance objectives (i.e., specified in the controls managers apply), subordinates are more confident that authorities are committed to protecting and promoting their interests.
Keywords: Management